Outbreak of Fungemia among Neonates Caused by Candida haemulonii Resistant to Amphotericin B, Itraconazole, and Fluconazole - Khan, Zia U. (American Society for Microbiology, 2007)
The first outbreak of Candida haemulonii fungemia is described. The seven isolates from the blood of four neonates were identified by DNA sequencing of the ribosomal DNA. They were all resistant to amphotericin B, fluconazole, and itraconazole. This report highlights the emergence of C. haemulonii as an opportunistic pathogen in immunocompromised patients.